Proses Komunikasi Masyarakat Banjar Kaja, Sesetan, Denpasar Selatan, Bali dalam Mewariskan Nilai Tradisi Omed-omedan - Sunari Merta, Ni Made Ari Setia; Alit Suryawati, I Gusti Agung; Pradipta, Ade Devia (E-Jurnal Medium, 2017)
Communication and culture are two important things that are interrelated. Culture influences communication behaviour, while communication also determines, maintains, and bequeaths a culture. This research discusses how a culture, particularly a hereditary tradition, can be inherited through a process of communication within the society, in which the focus of tradition in this study is Omed-omedan in Banjar Kaja, Sesetan, South Denpasar, Bali. This study is aimed at observing and describing the process of communication in the society of Banjar Kaja, Sesetan, and also the ongoing strategy for bequeathing the value of this tradition. The method that used in this study was qualitative method, using descriptive approach. The technique of data analysis used was interactive model analysis, by Miles and Huberman, with the conclusion was done inductively through some steps, namely data collection was done through deep interview, supported by participatory observation technique and document study. The result of this study shows that the effort of people in Banjar Kaja, Sesetan in bequeathing the value of this tradition involves the process of value injection and the process of strengthening the tradition value in which those processes take place in three components, namely the family, sekaa truna, and the society. These communication process occurred in three components are the uniques strategy possessed by the people there to bequeath the tradition value to their generation in Banjar Kaja. The tradition value includes the value of fertility (the meeting of purusa and pradana), the value of purity (the use of water in tradition process), the value of belief in self-recovery, and the value of protection (the belief of any phenomenon happens).     Keywords : Communication process, inheritance of value, omed-omedan